The prognostic impact of C‐reactive protein and albumin in patients diagnosed with acute myeloid leukaemia - Espen Talseth Skar; Øystein Wendelbo; Håkon Reikvam (eJHaem, 2024)
Abstract Background Acute myeloid leukaemia (AML) is an aggressive and heterogeneous malignant disease. Patient age, comorbidities and disease‐specific genetic abnormalities are recognized as primary determinants of treatment response. Recent years have elucidated the significance of nutritional status and inflammation across various malignancies, including AML, in influencing treatment outcomes. Aims To assess the prognostic value of the C‐reactive protein‐albumin ratio (CAR) and the Glasgow Prognostic Score (GPS) in predicting overall survival (OS) rates among patients diagnosed with AML. Material and methods 189 AML patients receiving standard cytarabine and anthracycline‐based induction treatment were included. Baseline demographic, clinical and laboratory data were collected, and treatment outcomes and survival were registered for all patients. Results No significant association between CAR and prognosis among AML patients was found, even in subgroup analyses. Hypoalbuminemia was an independent predictor of poor survival among all patients (OS 28 vs. 16 months; p < 0.02). Patients with a GPS of 0 or 1 demonstrated superior OS compared to those with a GPS of 2 (median OS 28 vs. 16 months, respectively; p = 0.015). Results remained consistent among patients ≥ 60 years (median OS 15 vs. 6 months; p = 0.020). Conclusion Heightened inflammation and suboptimal nutritional status correlate with unfavourable prognoses in AML patients. Such insights hold the potential for guiding clinical decision‐making, offering easily accessible prognostic information for the induction treatment of eligible AML patients.